Invasive bladder urothelial carcinoma, plasmacytoid variant: case report - Rui Pedro C. M. Oliveira; Carlos Filipe C. Abrantes; Edgar Miguel C. T. Silva; Carol A. Marinho; Vítor Manuel L. Sousa; Lígia R. C. O. A. P. Castro
ABSTRACT Invasive bladder urothelial carcinoma, plasmacytoid variant is a rare entity with scarce cases reported in the literature. We report a case of a 79 years old male, subjected to transurethral resection of bladder tumor, which histological examination revealed a pT1 high-grade urothelial carcinoma. Subsequently, he underwent radical cystoprostatectomy, which showed urothelial carcinoma with lack of cohesion, plasmacytoid variant, positive for citokeratin 7 (CK7), citokeratin 20 (CK20) and trans-acting T-cell-specific transcription factor (GATA-3), and negative for E-cadherin and CD138. It is important to recognize the plasmacytoid variant of the invasive urothelial carcinoma, since it avoids a potential misdiagnosis of metastatic cancer.